2006
DOI: 10.1098/rsta.2006.1774
|View full text |Cite
|
Sign up to set email alerts
|

Two fluid compartments in the renal inner medulla: a view through the keyhole of the concentrating process

Abstract: Approximately four decades ago, the countercurrent theory became influential in studies on the concentrating process in the mammalian kidney. The theory successfully represented the concentrating process in the outer medulla, but the problem of the concentrating mechanism in the inner medulla, as defined by Homer Smith has remained essentially intractable. In a recent comprehensive review by Knepper and coworkers of various theories and models, attention was refocused on the possible role of hyaluronate (HA) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
(66 reference statements)
0
7
0
1
Order By: Relevance
“…This would in turn raise the luminal osmolality above that of the interstitium and generate a single effect for concentration of urine. However, thermodynamic analysis of this process indicates that the pressures exerted on the inner medullary tissue can only account for a small fraction of the concentrating work in the inner medulla (70,100). Very recently, Pinter and Shohet (69) suggested that pelvic contractions could contribute to the IM osmolality gradient via a different mechanism, one based on the Gibbs-Donnan effect between two interstitial compartments, one containing hyaluronan and the other extravasated plasma albumin.…”
Section: How Can the Kidney Produce Highly Concentrated Urine?mentioning
confidence: 98%
“…This would in turn raise the luminal osmolality above that of the interstitium and generate a single effect for concentration of urine. However, thermodynamic analysis of this process indicates that the pressures exerted on the inner medullary tissue can only account for a small fraction of the concentrating work in the inner medulla (70,100). Very recently, Pinter and Shohet (69) suggested that pelvic contractions could contribute to the IM osmolality gradient via a different mechanism, one based on the Gibbs-Donnan effect between two interstitial compartments, one containing hyaluronan and the other extravasated plasma albumin.…”
Section: How Can the Kidney Produce Highly Concentrated Urine?mentioning
confidence: 98%
“…The extravasated albumin molecules are mobile and, driven by solvent drag, move rapidly through their EPA compartment and re-enter into the ascending vasa recta [17, 18]. We estimated [10] that the EPA compartment constitutes approximately 15–20% of the interstitial volume, and cited experimental data [19, 20] indicating that the concentration of albumin molecules in this compartment is about one third to one half of that in circulating plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Knepper et al [9] proposed that a macromolecule, hyaluronan (HA), played the role of a mechano-osmotic transducer in the process. In an earlier paper [10] we discussed the role of macromolecules in the inner medulla and argued that by considering the thermodynamic equivalence between mechanical and osmotic work, the work exerted by the pelvic muscles seemed disproportionately small to account for the increase of solute concentration occurring in the inner medulla. The hypothesis developed here provides a possible resolution of this discrepancy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…El lector interesado puede recurrir a la bibliografía sobre el tema. [21][22][23] b. L a a c c i ó n d e l a v a s o p r e s i n a s o b r e el receptor V2 extrarrenal estimula la producción de factores de la coagulación: factor VIIIc y Von Willebrandt. Sus niveles aumentan dos a tres veces sobre los basales.…”
unclassified